Europejskie portfolio językowe jako instrument samooceny prac pisemnych na poziomie zaawansowanym w nauce języka obcego - Krzemińska, Katarzyna (Neofilolog, 2019)
The purpose of this article is to explore the role of the ELP in teaching language skills to students of foreign languages, in my professional situation – to German Language and Literature students. The article attempts to answer the following questions: To what extent do the ELP and the Council of Europe documents help students of foreign languages use self-evaluation? How do these documents support learner autonomy? Due to the growing interest in the ELP, I focused my attention on the use of self-evaluation skills by college students during their writing tasks. The article presents the results of a study on self-evaluation. It was carried out among first and second year students of German Language and Literature Studies at the State Higher Education College in Włocławek in the academic years 2005/2006 and 2006/2007.